Effectiveness of Simple Patent Protection Based on Traditional Knowledge of Creative Economic Products - Saddam Syahbani Nasution; Erika Lismayani; Candra Kusuma Negara (LEGAL BRIEF, 2022)
The influence of technological developments has been tremendous on daily life in recent years, and the product is very rapid. These developments are not only supported by high technology, such as computers, electricity, telecommunications and biotechnology but also in the fields of mechanics, chemistry and others. In fact, along with that, awareness is also increasing to increase the utilization of simple technology. Indonesia already has a law that specifically provides legal protection for inventors in various fields of technology; the law in question is Law Number 13 of 2016 concerning Patents. The law also manifests Indonesia's commitment to implementing the Agreement Establishing the World Trade Organization, which contains the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPs), which regulates patent issues. It is hoped that with the enactment of the Patent Law in Indonesia, public legal awareness about understanding Patents, especially Simple Patents, will be higher. To optimize it, efforts need to be made to encourage the public to produce inventions to be patented so that people can experience the economic benefits of simple patents based on traditional knowledge. Patents can protect the cultural diversity and traditional knowledge we have to advance Indonesia's economic growth level. Our traditional knowledge can become a creative economy, understanding the monetary value of this traditional knowledge that we have not optimized. Indonesian conventional version must be developed and empowered sustainably so that Indonesia can compete globally.